Palatability and physical properties of potassium-binding resin RDX7675: comparison with sodium polystyrene sulfonate - Zann V; McDermott J; Jacobs JW; Davidson JP; Lin F; Korner P; Blanks RC; Rosenbaum DP (Dove Medical Press, 2017)
Vanessa Zann,1 John McDermott,1 Jeffrey W Jacobs,2 James P Davidson,2 Fangling Lin,2 Paul Korner,2 Robert C Blanks,2 David P Rosenbaum2 1Quotient Clinical, Nottingham, UK; 2Ardelyx Inc., Fremont, CA, USA Background: Hyperkalemia is a potentially life-threatening condition that patients with heart failure or chronic kidney disease, especially those taking renin–angiotensin–aldosterone system inhibitors, are at high risk of developing. Sodium polystyrene sulfonate (SPS), a current treatment, binds potassium within the gastrointestinal tract to reduce potassium absorption. However, poor palatability limits its long-term use. RDX7675, a novel potassium binder in development for the treatment of hyperkalemia, is a calcium salt of a reengineered polystyrene sulfonate-based resin designed to have enhanced palatability. Here, the physical properties and palatability of RDX7675 and SPS are compared.Methods: RDX7675 and SPS particle sizes were measured using wet dispersion laser diffraction. Palatability was assessed in a randomized, crossover, healthy volunteer study with two visits. At visit 1 (open label), volunteers evaluated high-viscosity, intermediate-viscosity, and water-reconstituted formulations of RDX7675 (all vanilla flavor), and an equivalent reconstituted SPS (Resonium A®). At visit 2 (single-blind), volunteers evaluated RDX7675 as a high-viscosity formulation in vanilla, citrus, and mint flavors, and as intermediate-viscosity, low-viscosity, and reconstituted formulations in citrus flavor. Volunteers used a “sip and spit” technique to rate overall acceptability and seven individual characteristics from 1 (“dislike everything”) to 9 (“like extremely”).Results: RDX7675 particles were smaller than SPS particles, with a narrower size range (RDX7675, 80%, 14–52 µm; SPS, 11.3–124.2 µm), and had a smooth, spherical shape, in contrast to the shard-like SPS particles. Reconstituted RDX7675 was considered superior to SPS for five of the seven palatability characteristics and for overall acceptability (median, visit 1: reconstituted RDX7675, 5.0; SPS, 4.0). High-viscosity vanilla was the most highly rated RDX7675 formulation (median overall acceptability, visit 2: 7.0).Conclusion: The smaller, more uniformly shaped, spherical particles of RDX7675 resulted in improved palatability over SPS when reconstituted in water. The overall results are promising for future patient acceptability of RDX7675 treatment. Keywords: hyperkalemia, potassium, heart failure, chronic kidney disease, adherence, drug formulation